ANALISIS MASA SIMPAN PRODUK SAMBAL TEMPOYAK BERPOTENSI SEBAGAI PRODUK OLEH-OLEH BARU - Dini Junita; Maryam Novitasari (Jurnal Akademika Baiturrahim Jambi, 2019)
Tempoyak is one of traditional food from Jambi Province. The innovation product of tempoyak that commonly consumption in community is Sambal Tempoyak. The processing of tempoyak into sambal is intended to improve the taste, but the shelf life is short. Vacuum packaging is expected to be able to maintain the quality of Sambal Tempoyak. This quantitative experimental research is analyzed descriptively to draw conclusions. Tempoyak used in this research comes from traditional markets in the Jambi city. Sambal tempoyak made with herbs and spices adding. After cooked and cooled, the sambal tempoyak was packed with plastic and vacuumed using a vacuum sealer. The products storage in two temperatures; room temperature and cold temperatures and then, test of levels of microbial contamination using the Total Plate Count test. Test starting from the first day of processing (0 days of storage), 7th day, 14th day, and  21th day. The results showed the number of sambal tempoyak microbes stored at room temperature lower than sambal tempoyak which is stored in the refrigerator temperature and storage age of the product until the 21st day after processing, but Klabsiella Ozaenae contamination occurred in the 14th day sample. Further research, suggested to examine the  bacteria that contaminate this product so the prevention about this bacterial can applied by hazard analysis critical control point.